History Learning Based On Digital Catalog Media In Increasing Student's Historical Awareness - Zubaidah, Nanik; Arif Musadad, Akhmad; yanto, Sudi (CV. Inara, 2022)
History learning is a field of science that aims to build student awareness about the importance of time and place of a process from the past, present, and future. Student awareness of history shows that they are a part of Indonesia who has a sense of pride and love of the homeland that can be implemented in various national and international lives. This article aims to discuss history learning based on digital catalog media that is useful for the teaching and learning process to help students to understand learning to increase their historical awareness. The research is classroom action research. The findings suggest that history learning is essential for students, the use of catalog media in history learning is very helpful to facilitate the teaching and learning process and help students to know, understand, and apply the attitude of historical awareness in everyday life.